Understanding the environmental factors related to the decrease in Pediatric Emergency Department referrals for acute asthma during the SARS‐CoV‐2 pandemic. Issue 1 (4th October 2021) - Dondi, Arianna; Betti, Ludovica; Carbone, Claudio; Dormi, Ada; Paglione, Marco; Rinaldi, Matteo; Gualtieri, Maurizio; Scotto, Fabiana; Poluzzi, Vanes; Fabi, Marianna; Lanari, Marcello
Abstract: Background: Lockdown measures during the SARS‐CoV‐2 pandemic determined radical changes to behavioral and social habits, that were reflected by a reduction in the transmission of respiratory pathogens and in anthropogenic atmospheric emissions. Objective: This ecological study aims to provide a descriptive evaluation on how restrictive measures during the SARS‐CoV‐2 pandemic impacted Pediatric Emergency Department (PED) referrals for asthma exacerbations, and their potentially associated environmental triggers in Bologna, a densely populated urban area in Northern Italy. Methods: Files of children evaluated for acute asthma during 2015 to 2020 at the PED of Sant'Orsola University Hospital of Bologna were retrospectively reviewed. Historical daily concentration records of particulate (PM2.5, PM10 ) and gaseous (NO2, C6 H6 ) air pollutants, and pollen were concurrently evaluated, including specific PM chemical tracers for traffic‐related air pollution (TRAP). Results: In 2020, asthma‐related PED referrals decreased compared to referral rates of the previous 5 years ( p < 0.01). This effect was particularly marked during the first lockdown period (March to May), when the drastic drop in PED referrals was associated with a reduction of high‐priority cases up to 85% and by 54%, on average. A concomitant reduction in the concentrations of traffic‐related air pollutants was observed in the range of 40%–60% ( p < 0.01). Conclusions: The lower rate of asthma exacerbations in childhood was in this study paralleled with reduced TRAP levels during the pandemic. Synergic interactions of the multiple consequences of lockdowns likely contributed to the reduced exacerbations, including decreased exposure to ambient pollutants and fewer respiratory infections, identified as the most important factor in the literature.